2020
DOI: 10.2174/1389201020666190822161337
|View full text |Cite
|
Sign up to set email alerts
|

Coffea arabica Bean Extracts and Vitamin C: A Novel Combination Unleashes MCF-7 Cell Death

Abstract: Background:: Vitamin C (VC) is believed to enhance immunity and is regularly integrated as a supplementary agent during several treatments. Objective:: The green (GC) and roasted (RC) coffee (Coffea arabica) aqueous extracts (0, 125, 250 and 500 μg/ml) combined with VC (50 μg/ml) were examined on the cancerous MCF-7 cell line and normal human lymphocytes. Methods:: Neutral red uptake assay, comet assay, immunocytochemical reactivity for protein expression and mRNA expression of apoptosis-related genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Several herbal extracts showed promising potent scolicidal and antischistosomal effects [42,43]. The herbs' protective potentials against various toxic agents [44][45][46][47], anticancer activities towards many types of cancers and anti-inflammatory properties [48][49][50][51][52][53][54] were also reported in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Several herbal extracts showed promising potent scolicidal and antischistosomal effects [42,43]. The herbs' protective potentials against various toxic agents [44][45][46][47], anticancer activities towards many types of cancers and anti-inflammatory properties [48][49][50][51][52][53][54] were also reported in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In Prochilodus lineatus fish, MN and DNA damage were evidenced in the erythrocytes as a result of Imid exposure 7,25 . Vitamin C, chemically known as ascorbic acid (Asc), is well known for its strong antioxidant potency [26][27][28] . It is a good reducing agent and inhibits lipid peroxidation 29 , and even in small doses, its effectiveness for redox recycling was proved 30 .…”
mentioning
confidence: 99%
“…Ratanamarno et al [5] reported that catechin (C, 6), epicatechin (EC, 7), epicatechin gallate (ECG, 8) and epigallocatechin gallate (EGCG, 9) in fresh C. arabica L. leaves. Chen et al identified delphinidin 3,5-diglucoside (10) and delphinidin 3-(6"-malonyl-glucoside) (11) in the young leaves of C. arabica L. [6] Besides the above mentioned constituents, flavonoids and their glycosides were also isolated from the leaves of C. arabica L., which were named as cyanidin-3-O-Glu (12), cyanidin-3-O-rutinoside (13), kaempferol (14), kaempferol-3-O-Glc (15), kaempferol-3-O-Glc-Hex-DeHex (16), kaempferol-3-O-Glc-Hex (17), kaempferol-3-O-Glc-(6''-Rha) (18), quercetin (19), quercitrin (20), isoquercitrin (21), rutin (22), hyperoside (23), quercetin-3-O-Glc-Hex-DeHex (24), quercetin-3-O-Glu (25), luteolin (26), patuletin (27), fisetin (28), myricetin (29) and apigenin (30). [6][7][8][9] Their structures are shown in Figure 2.…”
Section: Flavonoidsmentioning
confidence: 99%
“…According to a new study by Ei-Garawani, apoptotic anticancer pathway of the green and roasted C. arabica L. aqueous extracts combined with VC was examined on the cancerous MCF-7 cell line and normal human lymphocytes. [20] Antidiabetic activity Sake et al [21] found that C. arabica L. bean and leaf extract showed a high decrease in blood glucose levels compared to the control group. Mellbye et al [22] found cafestol could increase glucose-stimulated insulin secretion in vitro and increase glucose uptake in human skeletal muscle cells.…”
Section: Antioxidation Activitymentioning
confidence: 99%